If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(3d + -2) + 4d = 2(2d + 1) + -3d Reorder the terms: 5(-2 + 3d) + 4d = 2(2d + 1) + -3d (-2 * 5 + 3d * 5) + 4d = 2(2d + 1) + -3d (-10 + 15d) + 4d = 2(2d + 1) + -3d Combine like terms: 15d + 4d = 19d -10 + 19d = 2(2d + 1) + -3d Reorder the terms: -10 + 19d = 2(1 + 2d) + -3d -10 + 19d = (1 * 2 + 2d * 2) + -3d -10 + 19d = (2 + 4d) + -3d Combine like terms: 4d + -3d = 1d -10 + 19d = 2 + 1d Solving -10 + 19d = 2 + 1d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-1d' to each side of the equation. -10 + 19d + -1d = 2 + 1d + -1d Combine like terms: 19d + -1d = 18d -10 + 18d = 2 + 1d + -1d Combine like terms: 1d + -1d = 0 -10 + 18d = 2 + 0 -10 + 18d = 2 Add '10' to each side of the equation. -10 + 10 + 18d = 2 + 10 Combine like terms: -10 + 10 = 0 0 + 18d = 2 + 10 18d = 2 + 10 Combine like terms: 2 + 10 = 12 18d = 12 Divide each side by '18'. d = 0.6666666667 Simplifying d = 0.6666666667
| 0=2+2x-4x^2 | | (2x-9)-(27-4x)=180 | | 2r+(5-r)=13+2r | | 5y+y=-14 | | -10=5a | | -3(-4w+1)+15=13w | | 5(x+1)+7=7x | | sr+t=u | | 14=-l/4 | | 19= | | -6(b+7)=-7b-37 | | -3(-4w+1)+15=13 | | 4=2(u-4)-8u | | 12.48+0.11=13.23+0.09 | | 8x-4y=-20 | | 21+2(21+3)+(4*21-5)=c | | 6-8(1+6x)=-2-4x | | 1/2(-2)= | | -5(-17-13d)=-4(10-15d) | | 5(2n-4)-3=-36-3n | | -36-4a=-4(8a-5) | | 4x+3+4x=-15 | | 0=-8m^2-2m+2 | | -15s=-75 | | -3/2m+2/3m=-1/2(1/2m-3/2)-8/3(1/2m+1) | | x-(12)=-4 | | 2x+(2/(2x-12)) | | -7(4t+14)=-20-15t | | -7x=-28+11-4 | | y-19.25=x^2+6x+30.25 | | 3-x=2(1-4x)-6 | | 7t-12-2t=9+5t |